Властивості покриттів сплавом цинк-нікель, осаджених при надграничних густинах струму - Майзеліс, Антоніна Олександрівна; Артеменко, Валентина Мефодіївна; Любімов, Андрій Ігорович (НТУ "ХПІ", 2017)
Методом анодної вольтамперометрії досліджено фазовий склад сплаву цинк-нікель, осадженого з низько концентрованого слабколужного полілігандного аміакатно-гліцинатного електроліту. Виявлено, що в покриттях, які отримані в умовах потенціодинамічного і потенціостатичного осадження при надграничних густинах струму (при потенціалах більш негативних за –1,4 В), значно збільшується вклад фази, збагаченої нікелем. З ростом товщини плівок сплаву спостерігається деякий зріст вмісту фаз при потенціалах початку катодної гілки вольтамперних залежностей і більш суттєвий – при потенціалі начала граничного струму. Покриття, осаджені при –1,45 В, містять менше 2 % фази, збагаченої цинком.

Phase composition of zinc-nickel alloy electrodeposited from a low-concentrated weakly alkaline polyligand ammonia-glycinate electrolyte is studied. Alloy coatings of different thicknesses were obtained under cyclic voltamperommetry (CVA) by scanning the potential to a given potential border in the cathode direction, and also with a potential delay at the cathode branch and in potentiostatic conditions. The phase composition of the alloys was determined by the method of anodic voltammetry in the same electrolyte. It was found that under conditions of CVA (when thin layers of the alloy were deposited), phases enriched with nickel appear at scanning potentials below –1.5 V. As the thickness of the films electrodeposited at the potential delay at the beginning of the cathodic branch of the CVA increases, a certain increase in the content of these phases is observed. At the over-limited current densities, which correspond to potential values below 1.3 V, the contribution of the phase enriched with nickel increases significantly. With increasing thickness of the alloy films, a certain increase in the phase content at the potentials of the onset of the cathode branch of the current-voltage dependences is observed, and a more significant one at the potential of the beginning of the limiting current. The coating deposited at –1.45 V contains less than 2 % of the phase enriched with zinc.
Properties of Zn-Ni alloy coatings, deposited under over-limited current density
Keywords: цинк-нікель; фазовий склад; анодна вольтамперометрія; аміакатно-гліцинатний електроліт; zinc-nickel; phase composition; anodic voltammetry; ammonia-glycinate electrolyte